RESTORAN HOOLA DENGAN DESAIN INTERIOR BERNUASA NATURAL - TRADISIONAL KALIMANTAN - Noviana dewi Harmoko; Gervasius Herry Purwoko; M. Y. Susan M. Y. Susan (Universitas Ciputra Surabaya, 2016)
In the early phase, Crino Interior Design Consultants will accept all kinds of projects, either in the form of commercial projects or residential projecst. In the second phase through the last one, it will focus on the commercial project and provide a design that contains customer experience, so the commercial project Hoola Restaurant is selected as the final project.The project be used as a lesson, experience, knowledge and design portfolio for the company.Culinary business is growing in big cities as well as in small developing cities. The community’s lifestyle that experiences a shift into favoring eating out as well as the lack of places of entertainment make restaurant one of the community’s destinations.With the increasing level of community’s interest on restaurants, more business persons will be interested in being engaged in this field. Hoola Restaurant needs unique and special features in comparison to the other business, which can be achieved by creating an interior design with an added value in the form of customer experience. Hoola Restaurant provides traditional food and uses the service system of self-service. The concepts that are supporting and suitable use in Hoola Restaurant are natural and traditional concepts. The interior design created is expected to realize the concepts and give an added value to Hoola Restaurant.